The evaluation of social fairness and residents' desirability perception of compact city living in Singapore - Golnaz Mortezaei, 1985-; Hasanuddin Lamit, supervisor; Fakulti Alam Bina (2011)
Thesis (Sarjana Sains (Rekabentuk Bandar)) - Universiti Teknologi Malaysia, 2011